2016
DOI: 10.18632/oncotarget.9353
|View full text |Cite
|
Sign up to set email alerts
|

Identification of polycystic ovary syndrome potential drug targets based on pathobiological similarity in the protein-protein interaction network

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common endocrinological disorders in reproductive aged women. PCOS and Type 2 Diabetes (T2D) are closely linked in multiple levels and possess high pathobiological similarity. Here, we put forward a new computational approach based on the pathobiological similarity to identify PCOS potential drug target modules (PPDT-Modules) and PCOS potential drug targets in the protein-protein interaction network (PPIN). From the systems level and biological background, 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Pathway analysis shows that the AGE-RAGE pathway is significantly active, which may promote inflammation, apoptosis, and vascular dysfunction [ 30 , 31 ]. In addition, highly active steroid hormone pathways include androgen receptor (AR) and progestin (PGR), reflecting hormonal disturbances in PCOS patients [ 32 , 33 ]. The pharmacological effects of WHQD involve several signaling pathways that are responsible for steroid hormone production, insulin resistance, and anovulation in women with polycystic ovary syndrome [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis shows that the AGE-RAGE pathway is significantly active, which may promote inflammation, apoptosis, and vascular dysfunction [ 30 , 31 ]. In addition, highly active steroid hormone pathways include androgen receptor (AR) and progestin (PGR), reflecting hormonal disturbances in PCOS patients [ 32 , 33 ]. The pharmacological effects of WHQD involve several signaling pathways that are responsible for steroid hormone production, insulin resistance, and anovulation in women with polycystic ovary syndrome [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hao Huang et al also reported a new computational approach to determine PPDT-Modules and PCOS potential drug targets in protein–protein interaction networks (PPIN). In their study, one PPDT-Module and 21 PCOS drug targets were identified, which 42 drugs targeting 13 PCOS drug targets (ESR1, RXRA, NCOA1, ESR2, THRB, RARA, PPARA, PPARG, PGR, ESRRG, RXRB, RARG, and VDR) were reported to be previously investigated experimentally [ 80 ]. Yu Wang et al also attempted to predict candidate target proteins related to PCOS and its known targets for clinical drugs and suggested some potential candidate targets, including ESR1, PGR, AR, AKR1C3, INSR, THRB, PTPN1, DPP4, NR3C1, HSD11B1, and METAP2 for berberine and other drugs related to PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium in a biomolecular system results from a balance between energy and entropy, and entropy‐driven structural and energy variations may be a critical factor to identify the active modules in biological networks. Many previous studies have discussed the conserved gene expressions or modules, but few methods have been exploited to measure the structural and energy variations of modules. Methods based on overlapping nodes or edges may not reflect the modular topological properties globally, and optimized models are required to quantitatively evaluate module variation from a topological structure and energy perspective.…”
Section: Discussionmentioning
confidence: 99%